Pulsed Electrical Discharges in Silicone Emulsion. Issue 3 (7th January 2014) - Miron, Camelia; Balan, Mihaela; Pricop, Lucia; Harabagiu, Valeria; Jepu, Ionut; Porosnicu, Corneliu; Lungu, Cristian Petrica
Abstract Pulsed electrical discharges were initiated between two tungsten electrodes immersed in silicone emulsion. Optical emission spectra have shown the formation of carbon and oxygen molecules and radicals. A broad emission continuum dominated the spectrum with the increase of the discharge time due to a transition to arc plasma. Two well‐distinguished and stable phases of different density were formed after the plasma treatment of the emulsion. Fourier transform infrared spectroscopy (FTIR), gel permeation chromatography (GPC), nuclear magnetic resonance spectroscopy (1H NMR) and surface tension measurements have shown that a demulsification of the silicone emulsion was achieved using this method.<inline-graphic xlink:href="ark:/27927/pgg4sxzdqxc" content-type="ppap201300048-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />